Black Intellectual Thought in Modern America : A Historical Perspective - Wendt, Simon; Smithers, Gregory D., 1974-; Behnken, Brian D. (Book collections on Project MUSE., 2017)
"Black intellectualism has been misunderstood by the American public and by scholars for generations. Historically maligned by their peers and by the lay public as inauthentic or illegitimate, black intellectuals have found their work misused, ignored, or discarded. Black intellectuals have also been reductively placed into one or two main categories: they are usually deemed liberal or, less frequently, as conservative. The contributors to this volume explore several prominent intellectuals, from such left-leaning leaders as W. E. B. Du Bois to conservative intellectuals like Thomas Sowell and from such well-known black feminists as Patricia Hill Collins to Marxists like Claudia Jones, to underscore the variety of black intellectual thought in the United States. Contributors also situate the development of the lines of black intellectual thought within the broader history from which these trends emerged. The result gathers essays that offer entry into a host of rich intellectual traditions."--